Edge reconstruction in fractional quantum Hall states - Sabo, Ron; Gurman, Itamar; Rosenblatt, Amir; Lafont, Fabien; Banitt, Daniel; Park, Jinhong; Heiblum, Moty; Gefen, Yuval; Umansky, Vladimir; Mahalu, Diana (Nature physics, 2017)
The nature of edge reconstruction in the quantum Hall effect (QHE) and the issue of where the current flows have been debated for years. Moreover, the recent observation of proliferation of ‘upstream’ neutral modes in the fractional QHE has raised doubts about the present models of edge channels. Here, we present a new picture of the edge reconstruction in two of the hole-conjugate states. For example, while the present model for ν = (2/3) consists of a single downstream chiral charge channel with conductance (2/3)( e 2 / h ) and an upstream neutral mode, we show that the current is carried by two separate downstream chiral edge channels, each with conductance (1/3)( e 2 / h ). We uncover a novel mechanism of fragmentation of upstream neutral modes into downstream propagating charge modes that induces current fluctuations with zero net current. Our unexpected results underline the need for better understanding of edge reconstruction and energy transport in all fractional QHE states. Two challenging questions related to the quantum Hall effect (QHE) are how edge reconstruction works and where the current flows. A new model now gives the answer for two types of QHE states — two separate downstream chiral edge channels are involved.